Effects of different starter culture combinations on fermented sausages - Gönülalan, Z; Arslan, A; Köse, A (Scientific Technical Research Council Turkey, 2004)
Commercial starter cultures containing (group A) S. xylosus DD-34 + P. pentosaceus PC-1, (group B) L. plantarum L74 + S. carnosus MIII, (group C) S. carnosus MIII + L. pentosus LP-1, (group D) S. xylosus DD-34 + P. pentosaceus PCFF-1, (group E) P. acidilactici PA-2, (group F) S. carnosus MC-1 + P. pentosaceus PC-1 and (group G) S. xylosus DD-34 + L. alimentarus BJ 33 were used for manufacturing fermented sausage. Sausage samples were examined for pH values, moisture contents, mesophilic aerobic bacteria, coliform bacteria, staphylococcus - micrococcus, lactobacillus, yeast and mould counts and sensorical characteristics on days 0, 1, 2, 3, 4 and 6 of the fermentation period. At the end of the fermentation period, pH values were 4.94 - 5.46, moisture contents were 36.15 - 39.77% and numbers of microorganisms were 7.88 - 9.96 log(10) cfu/g for mesophilic aerobic bacteria, 1.60 - 2.90 log(10) cfu/g for coliforms, 3.98 - 7.49 log(10) cfu/g for staphylococcus - micrococcus, 5.75 - 8.94 log(10) cfu/g for lactic acid bacteria and 3.31 - 3.96 log(10) cfu/g for yeast and moulds. Sensoric points were 7.30 - 8.67 for groups containing starter cultures and 5.57 for the control groups. It was concluded that starter culture combinations improve quality characteristics and have positive effects on some chemical and microbiological characteristics of rapidly ripened fermented sausage.
Farkli starter kültür kombinasyonlarinin fermente sucuklardaki etkileri
Keywords: fermented sausage; starter culture; quality